How do extrinsic cues influence consumers’ online hotel booking decisions? An event-related potential experiment - Feng, Ping; Wang, Jingqiang; Ding, Xin; Li, Cong; Guo, Fumei; Ding, Xinyi (Frontiers in Psychology, 2022)
When booking a hotel online, consumers are exposed to various cues such as online reviews and brand familiarity. This study aims to uncover the neural mechanism underlying online booking decisions based on these two cues. With the help of questionnaires and event-related potential (ERP) technology, this work conducted a 2 (brand familiarity: familiar vs. unfamiliar) ×2 (online review: positive vs. negative) within-subjects design. Behavioral results indicated that the booking rate in the positive reviews condition was higher than that of negative reviews; The response time in the familiar brands condition was longer than that of unfamiliar brands. ERP results showed that the P200 amplitude of familiar brands was smaller than unfamiliar brands while the LPP amplitude was the opposite. This suggested that in the early stage of cognitive processing, unfamiliar brands evoke more automatic and unconscious attention while in the later stage, familiar brands attract more conscious attention. In addition, this study also found that the N400 amplitude of negative online reviews was lager than that of positive online reviews, indicating that negative stimuli can result in a larger emotional conflicts than that of positive stimuli. This study provides new insights into the neural mechanism of online booking decisions in the hospitality.